Liver Abscess due to Fasciola hepatica: A Case Report of the North of Iran - Somaieh Matin; Farahnaz Joukar; Sara Yeganeh; Arash Daryakar; Fariborz Mansour-Ghanaei (Case Reports in Infectious Diseases)
One of the rare manifestations of fascioliasis is liver abscess. In this paper, we report the case of a 38-year-old woman with a liver abscess caused by Fasciola hepatica (F. hepatica). The patient was referred to the clinic with recurrent fever, right upper quadrant (RUQ) pain, and a large abscess in her liver. Despite the consumption of an antibiotic drug, she still had symptoms. The symptoms began to disappear upon starting the consumption of triclabendazole (TCBZ). Fascioliasis can manifest itself with unusual symptoms that provide no specific clue for its diagnosis. Therefore, it is important to consider F. hepatica in the differential diagnosis of liver abscess, especially in endemic regions.